2015
DOI: 10.1080/09168451.2015.1046363
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in antiproliferative activity of Angelica gigas Nakai by solid dispersion formation via hot-melt extrusion and induction of cell cycle arrest and apoptosis in HeLa cells

Abstract: Young Kim (2015) Improvement in antiproliferative activity of Angelica gigas Nakai by solid dispersion formation via hot-melt extrusion and induction of cell cycle arrest and apoptosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In addition to its potential use as a pharmaceutical agent, AGN is also marketed globally as a functional food product and AGN extract or AGN‐containing herbal mixtures are sold as dietary supplements for the relief of post‐menopausal symptoms, as a memory enhancer, and as a pain killer . AGN contains several active ingredients, including essential oils and polyacetylenes, in addition to coumarins (decursin and decursinol angelate); these are its major effective components . Extensive studies have been conducted on these substances, particularly on decursin and decursinol angelate, and numerous studies have reported their various pharmaceutical effects on human health …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its potential use as a pharmaceutical agent, AGN is also marketed globally as a functional food product and AGN extract or AGN‐containing herbal mixtures are sold as dietary supplements for the relief of post‐menopausal symptoms, as a memory enhancer, and as a pain killer . AGN contains several active ingredients, including essential oils and polyacetylenes, in addition to coumarins (decursin and decursinol angelate); these are its major effective components . Extensive studies have been conducted on these substances, particularly on decursin and decursinol angelate, and numerous studies have reported their various pharmaceutical effects on human health …”
Section: Introductionmentioning
confidence: 99%
“…2,9 Its dosage form is usually prepared by boiling the dried root in water to extract the effective ingredients. 2 In addition to its potential use as a pharmaceutical agent, AGN is also marketed globally as a functional food product 9,10 and AGN extract or AGN-containing herbal mixtures are sold as dietary supplements for the relief of post-menopausal symptoms, as a memory enhancer, and as a pain killer. 2 AGN contains several active ingredients, including essential oils and polyacetylenes, in addition to coumarins (decursin and decursinol angelate); these are its major effective components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among diverse phytomedicines for cancer prevention and therapy [ 16 , 17 , 18 ], the pharmacological effects of single components and extracts of Angelica gigas Nakai (AGN) have been widely investigated [ 19 ]. The main components of AGN, such as decursin (D) and decursinol angelate (DA), and its extracts have anticancer potentials in several types of cancers, such as breast, blood, cervical, colon, lung, oral, ovarian, prostate, and skin cancers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In our previous studies [ 22 , 24 , 26 ], AGN extract and AGN particles have shown anticancer activities in breast, buccal, and cervical cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite such advantages, the use of HME for treating vegetal products is still insufficiently explored. The literature has described only a few recent studies using curcumin [ 15 ], the herb Angelica gigas Nakai [ 16 ], and Ginkgo biloba [ 17 ]. All developed formulations have shown encouraging results for obtaining novel natural pharmaceutical products.…”
Section: Introductionmentioning
confidence: 99%